The Role of Local Institutions in Fisheries Business Activities in Pundata Baji Village, Labakkang District, Pangkep Regency - Aryadi, Didi; Arief, Andi Adri; Fachry, Mardiana E.; Ilyas, M. Irham; Alpiani, Alpiani; Amir, Faisal (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2025)
Local institutions are the values, rules, structures, and practices that exist within local communities and are interrelated with the activities carried out by a community. This study aims to determine the form and role of local institutions in fishing activities in Pundata Baji Village, Labakkang District, Pangkep Regency. This study was conducted from October 2024 to January 2025. This study used qualitative descriptive analysis and informant perception analysis using a Likert scale with data collection through interviews, observation, documentation, and literature study. The informants for this study were people whose livelihoods were in the fisheries sector, including fishermen, seaweed farmers, and fish farmers. During the field research, the researcher obtained 26 informants, and using the guidelines for determining informants, a total of 19 main informants were selected as references for providing information. The results of the study show that the existence of local community institutions such as punggawa sawi, sipakatongeng, nakasa, pappalele, and mabbulo sibatang in fishing activities plays an important role in the sustainability of the fishing industry. Local institutions act as a forum for coordination, a mechanism for profit sharing and economic roles, conflict management, collaboration and solidarity, and play a role in ecosystem sustainability. Local institutions are the values, rules, structures, and practices that exist within local communities and are interrelated with the activities carried out by a community. This study aims to determine the form and role of local institutions in fishing activities in Pundata Baji Village, Labakkang District, Pangkep Regency. This study was conducted from October 2024 to January 2025. This study used qualitative descriptive analysis and informant perception analysis using a Likert scale with data collection through interviews, observation, documentation, and literature study. The informants for this study were people whose livelihoods were in the fisheries sector, including fishermen, seaweed farmers, and fish farmers. During the field research, the researcher obtained 26 informants, and using the guidelines for determining informants, a total of 19 main informants were selected as references for providing information. The results of the study show that the existence of local community institutions such as punggawa sawi, sipakatongeng, nakasa, pappalele, and mabbulo sibatang in fishing activities plays an important role in the sustainability of the fishing industry. Local institutions act as a forum for coordination, a mechanism for profit sharing and economic roles, conflict management, collaboration and solidarity, and play a role in ecosystem sustainability.